Controlling System in Smart Agriculture for Automatic Monitoring of Plant Nutrition - Agustina, Dian Resha; Febrianti, Maria Shusanti; Susanty, Wiwin; Hindayanti, Kadek Setiani (Brilliance: Research of Artificial Intelligence, 2024)
Technological developments have had a major impact on the lifestyle of Indonesian people through sophisticated communication tools such as smartphones and gadgets. However, the use of this technology is still not optimal. In the Indonesian context, computer and information technology, especially Intelligent Systems, has changed the way people work, interact and live. One significant implementation of Smart Systems is Smart Agriculture, which uses information and communication technology to increase agricultural productivity. The application of Greenhouse technology and hydroponic methods in agriculture supports more efficient and productive plant growth. The use of TDS sensors to measure nutrient concentrations in water in the hydroponic method helps ensure optimal conditions. In this research, the automation of providing nutrition to lettuce plants has been carried out well according to predetermined conditions. The solution to solve the problem that occurs is to use an automatic nutrition system. This system can control the amount and frequency of nutrients provided accurately and efficiently, without depending on the skill and caution of the hydroponic farmer. In addition, this system also ensures that nutrients are provided consistently and safely for farmers and the environment. This technology utilizes sensors and automation systems to monitor nutritional conditions in the planting media in real-time and farmers can ensure that their plants receive the nutrients they need and have maximum yields. This system also helps farmers speed up the plant growth process and saves time and energy.